Reinfection, recurrence, or delayed presentation of COVID-19? Case series and review of the literature - Fatehi Elzein; Ahmed Ibrahim; Fatima Alshahrani; Mervat Mahrous; Esam Murshid; Turki Aldhehyan; Ghadah Almutiri; Meshal Altowairqi; Medina Ahmed; Mohammed Alsaeed; Eid Alsufyani; Nouf Alnawshan (Elsevier, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-cov-2), first described in December 2019, has now infected more than 28 million cases with almost one million deaths. Reinfection is not definitely established however disease recurrence is increasingly reported. Cases presentation: Four patients presented with a second episode of coronavirus disease 2019 (COVID-19) occurring 27-85 following their first illness. The initial episode was mild or asymptomatic while the second attack was severe requiring hospital admission. All four patients had a SARS-CoV-2 PCR test positive in the second episode. The chest-X-ray and/or computerized tomography (CT) scan showed bilateral alveolar shadows. Furthermore, the inflammatory markers were raised in the four patients. Three patients recovered following treatment with favipravir in addition tocilizumab and/or dexamethasone. Conclusion: Covid19 reinfection Recurrent COVID-19 is increasingly reported. However; other etiologies including superadded infection or pulmonary embolism should be ruled out, particularly if recurrence occurs less than 3 weeks.